Ethics in Biotechnology - K.C.A, Jalal; Jaswir, Irwandi (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
The most modern techniques in biotechnology owe their existence to the discovery of DNA cloning and the genetic manipulation of organisms. However Biotechnology is not new science In fact, many applications represent old practices with new methodologies. Human have been used organisms for their benefit in many processes for several thousand years. Therefore, one way of thinking about biotechnology is to consider two categories of activities: those that are traditional and familiar and those that are relatively new. Study of ethical and social concern in these categories makes this clear that there are many unanswered questions in this fields that requires caution regarding to public using of this technologies. Genetic manipulation (GM) especially cloning is a wonderful advancement in technology and knowledge. However, Professional and scientific societies should make clear that any attempt to create a child by somatic cell nuclear transfer and implantation into a woman’s body would be at this time an irresponsible, unethical, and unprofessional act. The environmental safety aspects of GM crops vary considerably according to local conditions. Different GM organisms include different genes inserted in different ways. This means that individual GM foods and their safety should be assessed on a case-by-case basis and that it is not possible to make general statements on the safety of all GM foods.